Field measurements of typhoon effects on a transmission tower and its modal parameter identification. Issue 8 (June 2020) - Li, Hong-Nan; Wang, Jin-Xin; Fu, Xing; Ren, Liang; Zhang, Qing
Many transmission towers have collapsed under typhoons in recent years, mainly due to the unclear behaviors of their structural properties, introducing many deficiencies in the design process. Therefore, implementing structural health monitoring is of great importance for investigating the structural features of large-span transmission lines. This study develops a stochastic subspace identification method to identify the modal parameters of transmission towers, and a finite element model of a transmission tower-line system is established based on a case in Guangdong Province, China. Moreover, a MATLAB program is written using the stochastic subspace identification method to perform a modal analysis on the wind-induced responses of a transmission tower, and the results are compared with those of the finite element model to verify the program's reliability. A structural health monitoring system installed on a transmission tower recorded the wind field data around the tower and its vibration responses during Typhoon Khanun. The characteristics of the typhoon wind field and the changes in the acceleration responses under different wind speeds were calculated, and the developed stochastic subspace identification method was used to identify the frequencies and damping ratios of the tower. The results show that the identified frequencies under different wind speeds in the longitudinal and transverse directions remain essentially unchanged, indicating that the monitoring tower was safe and suffered no damage during Typhoon Khanun. The damping ratios of the monitoring tower range from 1% to 4%, where the larger values may be caused by bolt slippage.